2011
DOI: 10.1128/ec.00210-10
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of Covalently Linked Cell Wall Proteins by Candida albicans Sap9 and Sap10

Abstract: The cell wall of the human-pathogenic fungus Candida albicans is a robust but also dynamic structure which mediates adaptation to changing environmental conditions during infection. Sap9 and Sap10 are cell surfaceassociated proteases which function in C. albicans cell wall integrity and interaction with human epithelial cells and neutrophils. In this study, we have analyzed the enzymatic properties of Sap9 and Sap10 and investigated whether these proteases cleave proteins on the fungal cell surface. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 73 publications
8
111
0
Order By: Relevance
“…However, only germinated cells exhibited this aggregation, suggesting that cell surface molecules that permit Sap6-mediated cell-cell aggregation are exposed upon germination. It is unclear from our experiments whether Sap proteinases have an enzymatic role in cell wall remodeling to expose these adhesins, either directly or through MAPK signaling (32,35), since experiments to epithelial cell monolayers were infected with the CAI4 and SAP deletion strains for 90 min. After extensive washing, the adherent cells were harvested using 0.1% Triton X-100 and plated on YPD agar plates, and the plates were incubated at 30°C for 24 h to determine the numbers of CFU of adherent fungal cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, only germinated cells exhibited this aggregation, suggesting that cell surface molecules that permit Sap6-mediated cell-cell aggregation are exposed upon germination. It is unclear from our experiments whether Sap proteinases have an enzymatic role in cell wall remodeling to expose these adhesins, either directly or through MAPK signaling (32,35), since experiments to epithelial cell monolayers were infected with the CAI4 and SAP deletion strains for 90 min. After extensive washing, the adherent cells were harvested using 0.1% Triton X-100 and plated on YPD agar plates, and the plates were incubated at 30°C for 24 h to determine the numbers of CFU of adherent fungal cells.…”
Section: Discussionmentioning
confidence: 98%
“…block Sap enzymatic activity with pepstatin A also inhibited germination. It is known that Sap9, a GPI-anchored cell wall proteinase, activates several cell surface proteins, including adhesins Ywp1, Hwp1, and Rbt1, by enzymatic cleavage (35). Thus, it is likely that Saps have dual roles, one enzymatic and involved in germination and a second, nonenzymatic, function for cell-cell aggregation that is mainly carried out by Sap6.…”
Section: Discussionmentioning
confidence: 99%
“…These proteinases are known to perform many cell wallrelated functions, ranging from maintenance of cell wall integrity to interaction with epithelial cells and the cleavage of cell surface-associated proteins. 29,30 They cleave the substrate at basic or dibasic residues, in contrast to the pepsin-like secreted proteinase Sap2, which prefers the presence of hydrophobic amino acids around the cleavage site. Secreted proteinases retained in the cell wall can thus increase the proteolytic activity associated with the surface of yeast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sap9 seems to be predominantly located in the cell membrane, and Sap10 is located in the cell wall and membrane [109] . Recently, Schild et al [110] demonstrated that Sap9 and Sap10 cleave covalently linked cell wall proteins, including chitinase Cht2 and the glucan-cross-linking protein Pir1. Deletion of the SAP9 and SAP10 genes resulted in a reduction of cell-associated chitinase activity similar to that upon deletion of CHT2, suggesting a direct influence of Sap9 and Sap10 on Cht2 function.…”
Section: F Pedrosoimentioning
confidence: 99%